PENGEMBANGAN MEDIA PEMBELAJARAN BERBABIS PERMAINAN DIGITAL ”BARET” BERDASARKAN KEMAMPUAN PENALARAN MATEMATIS BERBANTUAN UNITY - Rivaldi Adi Saputra; Dori Lukman Hakim (Universitas Bhinneka PGRI, 2024)
Effective education that supports future development is the type of education that focuses on developing students' abilities. Developing digital game-based learning media can be an innovative choice to expand digital media and add variety to the learning process, especially in mathematics education. This digital media development uses the Unity platform and follows the Research and Development (RD) method with the 4D model. The research results show that the development of the